PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN AUDIOVISUAL DENGAN KERAMAH TERHADAP PENGETAHUAN PERTOLONGAN PERTAMA PADA KECELAKAAN DI BANJAR PANGI, PIKAT, DAWAN, KLUNGKUNG, BALI - judha, Mohamad; erikawati, luh; iwan, deden (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2024)
Background: The number of traffic accidents in 2017 was 103,228 incidents1. Nearly 90% of victims who died or were disabled were because they had passed the golden period. Objective: To find out the influence of health education using the lecture method using audiovisual media on knowledge of first aid in traffic accidents by the people of Pikat, Dawan, Klungkung, Bali. Research Method: This type of research is quantitative with a quasi experimental method. The research design used was pre and post test with control. The research sample was 32 in each group using purposive sampling technique. The treatment group was given education using audiovisuals with lectures and the control group was only given lectures. Data analysis used Wilcoxon, paired T test and effectiveness test using Mann Whitney. Results: The results of the analysis showed an increase in knowledge scores after being given health education in the treatment group, an average of 21.65 with a p-value of 0.000 and in the control group there was an increase in the average knowledge score of 13.52 with a p-value of 0.000, results The effectiveness test obtained a p-value of 0.000. Conclusion: There was a significant increase in scores in both the intervention and control groups, however the intervention group which was given audiovisual lectures was more effective in increasing knowledge than the control group